2017
DOI: 10.1242/jcs.203992
|View full text |Cite
|
Sign up to set email alerts
|

An essential role of CBL and CBL-B ubiquitin ligases in mammary stem cell maintenance

Abstract: There was an error in Development (2018Development ( ) 144, dev138164 (doi: 10.1242.One of the author names was spelled incorrectly. The online version has been corrected. The authors apologise to readers for this mistake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
(41 reference statements)
0
3
0
Order By: Relevance
“…Indeed, expression of the oncogenic mutant PDGFRα Asp842Val, which localizes to the Golgi 239 and is the most common PDGFRα mutation in gastrointestinal stromal tumours 259 , promotes ciliary disassembly and cell proliferation by phenocoyping PDGF-DD-mediated signalling 246 . Furthermore, rapamycin-mediated inhibition of mTOR signalling, which is upregulated in cells deficient in both c-CBL and CBL-b 260 , rescues PDGF-AA–mediated signalling in IFT88 and IFT172 mutant fibroblasts that are devoid of primary cilia 250 , although further studies are required to understand the relationship between aberrant mTOR signalling and mislocalization of PDGFRα in the context of ciliary signalling and tumorigenesis. Finally, INPP5E, was suggested to control ciliary PDGFRα signaling by inhibiting PDGF-mediated AKT activation 261, 262, 263 .…”
Section: Ciliary Rtk Signallingmentioning
confidence: 99%
“…Indeed, expression of the oncogenic mutant PDGFRα Asp842Val, which localizes to the Golgi 239 and is the most common PDGFRα mutation in gastrointestinal stromal tumours 259 , promotes ciliary disassembly and cell proliferation by phenocoyping PDGF-DD-mediated signalling 246 . Furthermore, rapamycin-mediated inhibition of mTOR signalling, which is upregulated in cells deficient in both c-CBL and CBL-b 260 , rescues PDGF-AA–mediated signalling in IFT88 and IFT172 mutant fibroblasts that are devoid of primary cilia 250 , although further studies are required to understand the relationship between aberrant mTOR signalling and mislocalization of PDGFRα in the context of ciliary signalling and tumorigenesis. Finally, INPP5E, was suggested to control ciliary PDGFRα signaling by inhibiting PDGF-mediated AKT activation 261, 262, 263 .…”
Section: Ciliary Rtk Signallingmentioning
confidence: 99%
“…They are interlinked and opposing signalling pathways (González et al, 2020). Restrained mTOR activity is reported previously to be required for self-renewal and differentiation of mammary stem cells (Mohapatra et al, 2017). We and others have previously shown that AMPK activation leads to inhibiton of mTOR signaling in suspension (Saha et al, 2018a).…”
Section: Discussionmentioning
confidence: 64%
“…Although such organoids generally comprise the epithelial niche alone, Jamieson et al (2017) report in this issue the formation of mammary organoids from the adult mammary epithelium comprising both a secretory epithelium and a surrounding myoepithelial population. A second paper using mammary organoids identifies novel signalling requirements for epithelial stem cell maintenance during development and remodelling (Mohapatra et al, 2017). A non-epithelial population, the human umbilical cord-borne fibroblast, is also reported as capable of creating its own ossicle-bounded, marrow-forming niche (Pievani et al, 2017).…”
Section: Organoids For New Tissue Types and Improvements On Previous mentioning
confidence: 99%